The Effects of Online News Package Structure on Attitude, Attention, and Comprehension. (September 2016) - McIntyre, Karen; Barnes, Spencer R.; Ruel, Laura
Research has shown that website structure can impact storytelling. Based on theory regarding website interactivity and navigability, this study examined the effects of two online news packages' website designs—a multiple-page, nonlinear, click-through design and a single-page, linear, scroll-through design—on users' attitudes toward the website, factual and structural comprehension of site content, and attention to the site. Results of a 2 × 2 between-subjects experiment revealed that both types of comprehension were influenced by the interaction between website design and attention. Among participants who spent at least 10 min browsing, users were better able to recognize facts after looking at the scroll-through site, but they showed a deeper understanding of content after looking at the click-through site. Theoretical and practical implications for storytelling are discussed.